Internalisasi Nilai Empati dan Kepedulian Sosial melalui Festival Ramadhan dan Bakti Sosial pada Anak Usia Dini - Nabila Nur Saparwanti; Shilva Nuradillah; Siti Susanti; Siti Nazia Komalasari; Siti Bahar Shirin (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the process of internalizing empathy and social care values in early childhood through Ramadan Festival activities and social service programs in TK N Pembina Baros, Kota Sukabumi. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings indicate that Ramadan Festival activities such as creating Ramadan posters, making piggy banks, saving activities, preparing Ramadan parcels, sharing with people in need, and children’s creative performances are effective in instilling empathy and social care values. Children demonstrated behavioral changes, including increased caring attitudes, improved sharing abilities, and greater sensitivity to their social environment. Therefore, experience-based activities are considered effective in fostering social character development in early childhood.